2014
DOI: 10.5380/avs.v19i2.33351
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Quantitative Traits of Lamb Carcass of Three Subcutaneous Fat Thicknesses on the Loin

Abstract: The objective of this study was to evaluate productive and economic performances and quantitative carcass characteristics of ½Dorper + ½Santa Inês (½D-SI) and purebred Santa Inês (SI) lambs slaughtered with different subcutaneous fat thicknesses (SFT). Thirty-four lambs (16 SI and 18 ½D-SI) were confined and fed a total diet for an average daily weight gain of 0.300 kg. The subcutaneous fat thickness was measured by ultrasound (between the 12th and 13th ribs) and weekly weighing, and the lambs were slaughtered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 5 publications
2
6
0
1
Order By: Relevance
“…A similar growth rate was observed for the Cornigliese breed, with differences regarding gender and a proportional development of the head (Sabbioni et al, 2018). However, for lambs of other breeds finished in confinement (Furusho-Garcia et al, 2006) and slaughtered with different SFT (Mora et al, 2014), the neck cut showed isogonic growth. The shoulder cut presented a fast growth rate (β < 1) in relation to the development of the half carcass in lambs with 2.0 and 4.0 mm SFT.…”
Section: Resultssupporting
confidence: 71%
See 4 more Smart Citations
“…A similar growth rate was observed for the Cornigliese breed, with differences regarding gender and a proportional development of the head (Sabbioni et al, 2018). However, for lambs of other breeds finished in confinement (Furusho-Garcia et al, 2006) and slaughtered with different SFT (Mora et al, 2014), the neck cut showed isogonic growth. The shoulder cut presented a fast growth rate (β < 1) in relation to the development of the half carcass in lambs with 2.0 and 4.0 mm SFT.…”
Section: Resultssupporting
confidence: 71%
“…Unlike the other half-carcass cuts, the rib presented an isogonic growth in lambs slaughtered with 2.0 and 3.0 mm SFT. This same type of growth was observed for confined Texel x Ile de France (Galvani et al, 2008) and Pantaneiro (Mora et al, 2014) lambs, being considered unrelated to race. In the present study, an opposite result (β <1) was found for lambs slaughtered with 4.0 mm SFT.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations